Small extrachromosomal circular DNAs, microDNA, produce short regulatory RNAs that suppress gene expression independent of canonical promoters. Issue 9 (4th March 2019) - Paulsen, Teressa; Shibata, Yoshiyuki; Kumar, Pankaj; Dillon, Laura; Dutta, Anindya
Abstract: Interest in extrachromosomal circular DNA (eccDNA) molecules has increased recently because of their widespread presence in normal cells across every species ranging from yeast to humans, their increased levels in cancer cells and their overlap with oncogenic and drug-resistant genes. However, the majority of eccDNA (microDNA) in mammalian tissues and cell lines are too small to carry protein coding genes. We have tested functional capabilities of microDNA by creating artificial microDNA molecules mimicking known microDNA sequences and have discovered that they express functional small regulatory RNA including microRNA and novel si-like RNA. MicroDNA are transcribed in vitro and in vivo independent of a canonical promoter sequence. MicroDNA that carry miRNA genes form transcripts that are processed by the endogenous RNA-interference pathway into mature miRNA molecules, which repress a luciferase reporter gene as well as endogenous mRNA targets of the miRNA. Further, microDNA that contain sequences of exons repress the endogenous gene from which the microDNA were derived through the formation of novel si-like RNA. We also show that endogenous microDNA associate with RNA polymerases subunits, POLR2H and POLR3F. Together, these results suggest that microDNA may modulate gene expression through the production of both known and novel regulatory small RNA.